ANALISIS DIAZINON PADA TANAH LAHAN PERTANIAN MENGGUNAKAN KROMATOGRAFI CAIR KINERJA TINGGI - Marselina Theresia Djue Tea; Akhmad Sabarudin; Hermin Sulistyarti (Fakultas Pertanian, Universitas Timor, 2020)
A method for the determination of diazinon in soil samples has been developed. The analyte was extracted with acetonitrile from farmland soil sample. Determination and quantification of diazinon were perfomed by high perfomance liquid chromatography (HPLC) with an UV detector. Optimum conditions for diazinon analysis were eluent composition of acetonitrile:water ratio of 60:40, 0.4 mL/min of flow rate, and 220 nm of wavelength. Under the optimum conditions, diazinon linearity was between 1 and 25 mgL-1 with R2 of 0.9976, 1.19 mgL-1 LOD, and 3.98 mgL-1 LOQ. When the method was applied to the soil sample, both pesticides showed acceptable recoveries for real sample of more than 85%: thus, the developed method meets the validation requirement. Under this developed method, the concentrations of diazinon in the soil samples were below the LOD and LOQ (0.577 mgL-1). Therefore, it can be concluded that the soil samples used in this study did not contain diazinon.